Sekuritas Sosial Perempuan Rawan Sosial Ekonomi Pada Komunitas Nelayan Pulau Kecil (Kasus Pulau Salemo, Desa Mattiro Bombang, Kecamatan Liukang, Kabupaten Pangkajene Kepulauan, Sulawesi Selatan) - Hasbi, Hasbi Hasbi (Babes Litbang Yankessos, 2019)
Abstract In rural South Sulawesi there are 646, 210 thousand people or 12.30% of the poor. They are small farmers who do not have agricultural land and also small fishermen who do not have adequate fishing equipment so that it is not enough to guarantee basic needs his family. One group included in this category is Women Socio-Economic Prone (PRSE). The research objective is to describe social conditions economics of women socio-economic prone to fishing communities and describe social security practices in an effort to fulfill their basic needs. Research methods is qualitative descriptive with the type of case study. Data obtained through interviews depth and observation, then analyzed by means of data reduction, data presentation, and conclusion. The results of the study found that women were prone to socio-economic conditions in the fishing community on Salemo island, Mattiro Bombang village, Liukang sub-district is not able to fulfill their basic needs. In practice social security applies the principle of lead balik (situlung-tulung), love each other (sipammase-mase), appropriateness (assitinajang), mutual visit (silokkai). Suggestions to the government, careful arrangement needs to be done about the category of poor and mediocre women in socio-economic vulnerability, it needs to improve budget allocation to increase income so that they no longer owe it to paggadde-gadde, increasing allocations for education, health, clean water, and the environment. Keywords: social security; women prone to socio-economic; small island fishermen. Abstrak Di pedesaan Sulawesi Selatan terdapat 646,210 ribu jiwa atau 12,30% penduduk miskin. Mereka adalah petani kecil yang tidak memiliki lahan pertanian dan juga nelayan kecil yang tidak memiliki peralatan tangkap yang memadai sehingga tidak cukup menjamin kebutuhan dasar keluarganya. Salah satu kelompok yang termasuk dalam kategori tersebut adalah Perempuan Rawan Sosial Ekonomi (PRSE). Tujuan penelitian untuk mendeskripsikan kondisi sosial ekonomi Perempuan Rawan Sosial Ekonomi pada komunitas nelayan dan mendeskripsikan praktik sekuritas sosial dalam upaya pemenuhan kebutuhan dasar mereka. Metode penelitian adalah deskriptif kualitatif dengan jenis studi kasus. Data diperoleh melalui wawancara mendalam dan pengamatan, selanjutnya dianalisis dengan cara reduksi data, sajian data, dan penarikan kesimpulan. Hasil penelitian menemukan bahwa Perempuan Rawan Sosial Ekonomi pada komunitas nelayan di pulau Salemo, desa Mattiro Bombang, kecamatan Liukang tidak mampu memenuhi kebutuhan dasarnya. Dalam praktik sekuritas sosial berlaku prinsip timbal balik (situlung-tulung), saling mengasihi (sipammase-mase), kepantasan (assitinajang), saling mengunjungi (silokkai). Saran kepada pemerintah, perlu dilakukan penataan secara cermat tentang kategori Perempuan Rawan Sosial Ekonomi miskin dan pas-pasan., perlu meningkatkan alokasi anggaran untuk meningkatkan pendapatan sehingga mereka tidak lagi berhutang pada paggadde-gadde, meningkatkan alokasi untuk pendidikan, kesehatan, air bersih, dan lingkungan. Kata Kunci: sekuritas social; perempuan rawan sosial ekonomi; nelayan pulau kecil.